Taxation, Time Allocation and Externalities - Nielsen, Jens Erik; Pilegaard, Ninette (Proceedings from the Annual Transport Conference at Aalborg University, 2004)
Using the approach introduced in Becker (1965) this paper derives rules for optimal taxation in the presence of externalities. The same was done in Kleven (2004) in the case where externalities were excluded resulting in the inverse factor share rule for optimal taxation. This rule states that fast cars should carry a lower tax rate than slow cars because of time savings. Including externalities modifies the result and gives a simple extension to the tax formulae. The results emphasize that taxation of externalities and revenue-generating taxation of goods should not be looked on separately.